STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM; STUDI LAPANGAN DI MIS NURUL MUHSININ BATUJAI - Siti Rohani (Journal of Education, Teaching, and Learning, 2025)
This study aims to analyze strategies to improve the quality of Islamic Religious Education (PAI) learning at MIS Nurul Muhsinin Batujai. Various challenges such as limited learning methods, lack of innovation in learning media, and low parental participation are obstacles in improving the quality of learning. This study uses a qualitative approach with a field study method. Data collection techniques include observation, interviews, and documentation. The research subjects consisted of the head of the madrasah, PAI teachers, students, and parents as parties who play a role in supporting PAI learning. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the strategy to improve the quality of PAI learning at MIS Nurul Muhsinin Batujai involves several aspects, including: the use of active learning methods such as interactive lectures, discussions, and worship practices; the use of technology-based learning media to increase student interest in learning; and strengthening parental involvement in supporting learning at home. In addition, improving teacher competence through training and workshops is also an important factor in increasing the effectiveness of PAI learning. This study confirms that the implementation of a comprehensive strategy, including innovation in learning methods, strengthening the role of teachers and parents, and utilizing relevant learning media, can improve the quality of Islamic Religious Education learning at MIS Nurul Muhsinin Batujai